Advancing new diagnostic tests for latent tuberculosis infection due to multidrug-resistant strains of Mycobacterium tuberculosis — End of the road?. (March 2020) - Mwaba, Peter; Chakaya, Jeremiah Muhwa; Petersen, Eskild; Wejse, Christian; Zumla, Alimuddin; Kapata, Nathan
Abstract: An estimated 1.8 billion people worldwide have a latent tuberculosis infection (LTBI), with wide variations in LTBI rates across countries. LTBI can be due to infection with either drug-sensitive or drug-resistant Mycobacterium tuberculosis (Mtb) strains. Accurate data on the prevalence of LTBI due to multidrug-resistant (MDR) Mtb strains are unavailable, since the strains cannot be isolated for resistance testing. There are no 'gold standard' tests for accurately diagnosing LTBI. Only three tests are currently available and approved by the World Health Organization (WHO) for the diagnosis of LTBI: the now outdated tuberculin skin test (TST), developed a century year ago, and the two interferon-gamma release assays (IGRAs) developed and rolled out over the past decade, the QuantiFERON (Qiagen, Germany) and T-SPOT.TB (Oxford Immunotec, United Kingdom) tests. These latter tests are not ideal due to issues of sensitivity, specificity, inability to distinguish infection with MDR-Mtb strains, and high costs. Achieving the WHO End TB Strategy target of an 80% reduction in global TB incidence by 2030 will require a major reduction in the number of persons with LTBI progressing to active TB disease. Critical to this will be the development of new diagnostic tests that are better than currently available LTBI tests at predicting who is at risk of progression to active TB disease. The diagnostic product development portfolio for LTBI appears to have reached the end of the road. Every attempt to make optimal use of currently available IGRAs using WHO LTBI guidelines for LTBI testing and treatment must be made to achieve WHO End TB strategy targets.